Protecting the Endothelial Cells, Reducing the Mortality of COVID-19 - Jianshe Yang (Diagnostic and Treatment Advances in COVID-19 and SARS-CoV-2, 2023)
As the current pandemic of SARS-CoV-2, physicians and hepatologists should be aware of the potential detrimental effects of this infection on the short-term outcome of such a fragile patient population. Especially, extra attention should be paid to the protection of endothelial cells, and actively respond to the acute inflammatory due to the endothelial cell injury. This would make a positive effect on the treatment of cirrhosis patients with SARS-CoV-2 infection and reduce the mortality of COVID-19.